The Influence of Employee Engagement on Employee Championing Behavior During Organizational Change - Christina Bardien; Damelina Basauli Tambunan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Organizational Change is one of the strategies carried out by companies to survive in difficult times, such as when companies have to survive during the Covid-19 pandemic. This study aims to examine whether there is an influence of Organizational Change on Employee Engagement and employee Championing Behavior and whether Employee Engagement has a mediating role between Organizational Change to Employee Championing Behavior in property companies in Makassar. The method of data analysis of this study using SmartPLS3 to perform Structural Equation Modeling (SEM) test. Data collection was conducted through a survey using a questionnaire with a Likert scale given to 59 respondents who are part of the employee population in property companies. The results of the study showed that Organizational Change has a direct effect on Employee Engagement and employee Championing. Good communication and getting employees involved in OC will increase the EE of employees. In addition, the behavior of the ECB will increase if the OC is well communicated, while Employee Engagement itself does not affect the behavior of the employee champion and also does not mediate the influence of the OC on the ECB.